Several different sequences are implicated in bloodstream-form-specific gene expression in Trypanosoma brucei - Bishola Tshitenge, Tania; Reichert, Lena; Liu, Bin; Clayton, Christine (PLoS neglected tropical diseases, 2022)
The parasite Trypanosoma brucei grows as bloodstream forms in mammalian hosts, and as procyclic forms in tsetse flies. In trypanosomes, gene expression regulation depends heavily on post-transcriptional mechanisms. Both the RNA-binding protein RBP10 and glycosomal phosphoglycerate kinase PGKC are expressed only in mammalian-infective forms. RBP10 targets procyclic-specific mRNAs for destruction, while PGKC is required for bloodstream-form glycolysis. Developmental regulation of both is essential: expression of either RBP10 or PGKC in procyclic forms inhibits their proliferation. We show that the 3’-untranslated region of the RBP10 mRNA is extraordinarily long—7.3kb—and were able to identify six different sequences, scattered across the untranslated region, which can independently cause bloodstream-form-specific expression. The 3’-untranslated region of the PGKC mRNA, although much shorter, still contains two different regions, of 125 and 153nt, that independently gave developmental regulation. No short consensus sequences were identified that were enriched either within these regulatory regions, or when compared with other mRNAs with similar regulation, suggesting that more than one regulatory RNA-binding protein is important for repression of mRNAs in procyclic forms. We also identified regions, including an AU repeat, that increased expression in bloodstream forms, or suppressed it in both forms. Trypanosome mRNAs that encode RNA-binding proteins often have extremely extended 3’-untranslated regions. We suggest that one function of this might be to act as a fail-safe mechanism to ensure correct regulation even if mRNA processing or expression of trans regulators is defective.